Implementasi Pusat Layanan Keluarga Sakinah (Pusaka Sakinah) di KUA Kecamatan Paciran Kabupaten Lamongan - Sutopo, Sutopo (Program Studi Hukum Keluarga Islam (HKI) dan bekerjasama dengan Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LP2M) Institut Pesantren Sunan Drajat Lamongan, 2024)
The Sakinah Family Service Center (Pusaka Sakinah) is a program initiated by the Ministry of Religion to strengthen family resilience through guidance and consultation services at the Office of Religious Affairs (KUA). This research aims to analyze the implementation of Pusaka Sakinah in KUA Paciran District, Lamongan Regency and its impact on the community. The research method used is descriptive qualitative. Data was obtained through in-depth interviews, observation and document analysis. The research results show that Pusaka Sakinah has played a role in providing marriage guidance services, family conflict mediation, and family resilience education.